2011
DOI: 10.1603/an11068
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Expression Pattern, and Phylogenetic Analysis of a Selenophosphate synthetase Gene from Antheraea pernyi (Lepidoptera: Saturniidae)

Abstract: Selenophosphate synthetase (Sps), the product of the SelD gene, produces a biologically active selenium donor compound from ATP and selenide. We have isolated and characterized the Sps gene from Antheraea pernyi (Guérin-Méneville) (Lepidoptera: Saturniidae), an economically important insect. The resulting 1601 bp cDNA sequence contains an open reading frame of 1209 bp encoding a polypeptide of 402 amino acids, with 87% sequence identity to that from Drosophila melanogaster (Meigen). Semiquantitative reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…) and selenophosphate synthetase (Sun et al . ) have been reported as a new molecular tool for phylogenetic inference. A total of 22 eukaryote organisms representative of MLC‐1 sequences from NCBI were used to construct a phylogenetic tree by the maximum likelihood method (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) and selenophosphate synthetase (Sun et al . ) have been reported as a new molecular tool for phylogenetic inference. A total of 22 eukaryote organisms representative of MLC‐1 sequences from NCBI were used to construct a phylogenetic tree by the maximum likelihood method (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many nuclear protein-coding genes, because they evolved more slowly, are less prone to base-composition bias than mitochondrial markers and typically present fewer alignment issues than ribosomal genes, have been used to reconstruct the phylogenetic relationships in eukaryotes (Wiegmann et al 2000;Lin & Danforth 2004;Danforth et al 2006). Several housekeeping genes have been reported and proposed for phylogenetic inference; for example, myosin heavy chain type II genes (Ruiz-Trillo et al 2002), ribosomal proteins (Shang et al 2005;Hou et al 2008), enolase (Regier et al 2009), lysophospholipase (Liu et al 2010b) and selenophosphate synthetase (Sun et al 2011) have been reported as a new molecular tool for phylogenetic inference. A total of 22 eukaryote organisms representative of MLC-1 sequences from NCBI were used to construct a phylogenetic tree by the maximum likelihood method (Fig.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…2010b ), topoisomerase and arginine kinase ( Wild and Maddison 2008 ), will die slowly ( Li et al. 2010 ), selenophosphate synthetase ( Sun et al. 2011 ), lysyl-tRNA synthetase ( Liu and Qin, 2011 ), and doba decarboxylase ( Regier et al.…”
Section: Resultsmentioning
confidence: 99%
“…2010b , Li et al. 2010 , Liu and Qin 2011 , Sun et al 2011 ). The eIF-4A gene has been isolated from various kinds of eukaryotes organisms.…”
mentioning
confidence: 99%